Research Productivity of Australian Planning Academics: A Bibliometric Analysis. (March 2022) - Pojani, Dorina; Olvera-Garcia, Jaime; Sipe, Neil; Byrne, Jason
The development of global metrics for evaluating university research performance has been accompanied by increasing attention to key performance metrics for individual disciplines. This paper examines research performance metrics for Australian planning academics. It addresses questions related to programs, staff, publications, and citations. The main findings are the following: Wide gender gaps exist in Australian planning academia; the mean number of publications is 36 per person, or 3 per person per year; the mean number of citations is 527 per person, or 48 per person per year; and planning journal impact factors are low (less than 3).